A molecular dynamics investigation on CO2–H2O–CH4 surface tension and CO2–CH4–H2O–graphite sheet contact angles - Yong, Wei; Wei, Zhi-jie; Liu, Yu-yang; Wang, De-qiang; Cui, Yong-zheng (Frontiers in Energy Research, 2023)
We perform Molecular Dynamics (MD) simulations of nanoscopic liquid water drops on a graphite substrate mimicking an organic-rich shale pore in the presence of CH4/CO2 mixtures at temperatures in the range 300 K to 473 K. Our results for the interfacial tension between water and methane as a function of pressure and for the interfacial tension between water and CH4/CO2 mixtures as a function of their composition agree well with the experimental and computational literature. The Modified Young’s equation has been proved to bridge the macroscopic contact angle and microscopic contact with experimental literature. The water droplet on both artificial textured surface and randomly generated surface exhibits a transition between Wenzel state and Cassie Baxter state with increased roughness height, indicating that surface roughness enhances the hydrophobicity of the solid surface.